Adoption of change in endodontic practice after an educational program: A qualitative study - Eva Wolf; Kerstin Leonard; My Vidigsson; Åke Tegelberg; Margaretha Koch (Wiley, 2022)
Abstract Objectives The aim was to define the characteristics of successful implementation of new clinical endodontic routines within a public dental health organization, following an educational program. Materials and Methods Fifteen staff members were strategically selected for the interview. All had completed a theoretical educational intervention including a complementary endodontic treatment strategy and, for the dentists, comprising training in the nickel‐titanium‐rotary‐technique. All experienced the successful acceptance of new clinical routines. Two thematic in‐depth audiotaped interviews were conducted, wherein the informants described the implementation process in their own words. The interviews were transcribed verbatim and analyzed according to Qualitative Content Analysis. Results A theme was identified: A multiple flexible process with governance support and gradual reinforcement of motivation, with the following main categories: Firstly, contextual facilitation, with two subcategories (i) a multifaceted organizational foundation and (ii) a tolerance of flexibility. Secondly, emotional facilitation, with two subcategories (i) an experience of simplification and (ii) an experience of improvement. Conclusion The results improve the understanding of a multifaceted process underlying the acceptance of changes to clinical endodontic procedures by dentists in a public dental health organization. Important contributing factors identified were governance support, a committed resource person with contextual knowledge, tolerance of flexibility in implementation, and permissive informal communication channels within the local workplace. These findings might be a valuable contribution to an evidence base, facilitating the selection of the most appropriate educational strategy and structure for a specified purpose.